The Fundamentals Of Gas Bubbling Into Liquid Metals - Roderick Guthrie (Metallurgy and Materials Society, 2013)
Three regimes of bubble formation in liquid metals, in terms of the mechanisms of bubble formation are reviewed. Towards this, bubble formation for a horizontal nozzle submerged in liquid pig iron was re-examined, for which an empirical correlation had been developed, correlating bubble size with gas flow rate, liquid metal surface tension, nozzle outer diameter and the capacitance number of the gas delivery system. Very good agreement between predicted and measured bubble size was obtained for non-wetting, ceramic-liquid metal systems. However, the question of how to create much smaller bubbles than those generally formed in liquid metals according to that work, is critically important. One method could be to create a submerged gas injection system by passing the gas entering the liquid metal through a narrow slot nozzle and make use of Rayleigh-Taylor instabilities. Ralph Harris has provided us with evidence to suggest that a carefully designed slot nozzle might serve as a candidate to create very small bubbles in liquid metals.